'You’re working, but you’re not working:’ Academic precarity, ambivalence and the use of researchers as factotums - Cairns, D. (British Journal of Sociology of Education, 2024)
This article explores an important aspect of academic precarity: the use of fixed-term contract researchers as factotums within universities. The practice can be defined as the taking-on of tasks that are outside of core research activities, including substantial amounts of time spent teaching, supervising students and preparing research proposals, often at the behest of tenured staff members, reflecting existing power dynamics within the organisation. At a theoretical level, it is argued that this aspect of academic precarity reflects various forms of ambivalence in researchers’ lives, creating tensions in addition to expanding their workloads. Using evidence from 54 interviews with researchers of at least five years’ experience and based at research units in Portugal, conducted during 2022 and 2023, it is possible to illustrate various aspects of academic precarity and ambivalence, with different responses from researchers including acceptance of and resistance towards the factotum role.